Polyvinylidene Fluoride Membrane Via Vapour Induced Phase Separation for Oil/Water Emulsion Filtration - Nawi, Normi Izati Mat (Polymers (Basel), 2021)
Membrane-based technology is an attractive option for the treatment of oily wastewater because of its high oil removal efficiency, small footprint and operational simplicity. However, filtration performance is highly restricted by membrane fouling, especially when treating oil/water emulsion as a result of strong interaction between oil droplets and the hydrophobic property of the membrane. This study explores the fabrication of polyvinylidene fluoride (PVDF)-based membrane via the vapour induced phase separation (VIPS) method while incorporating polyvinyl pyrrolidone (PVP) as a hydrophilic additive to encounter membrane fouling issues and improve membrane filterability. The resulting membranes were characterized and tested for oil/water emulsion filtration to evaluate their hydraulic, rejection and anti-fouling properties. Results show that the changes in membrane morphology and structure from typical macrovoids with finger-like substructure to cellular structure and larger membrane pore size were observed by the prolonged exposure time from 0 to 30 min through the VIPS method. The enhanced clean water permeability is attributed to the addition of PVP–LiCl in the dope solution that enlarges the mean flow pore size from 0.210 ± 0.1 to 7.709 ± 3.5 µm. The best performing membrane was the VIPS membrane with an exposure time of 5 min (M-5), showing oil/water emulsion permeability of 187 Lm(−2) h(−1) bar(−1) and oil rejection of 91.3% as well as an elevation of 84% of clean water permeability compared to pristine PVDF developed using a typical non-solvent induced phase separation (NIPS) method. Despite the relatively high total fouling, M-5 was able to maintain its high permeability by water flushing as a simple operation for membrane fouling control. The performance was achieved thanks to combination of the large mean flow pore size and hydrophilic property from residual PVP in the membarne matrix. Overall, the results demonstrate the potential of the optimum VIPS method in the presence of PVP and LiCl additives for oil/water emulsion treatment.